Advances in group processes. Volume 37 - Lawler, Edward J.; Thye, Shane R. (Bingley, U.K. : Emerald Publishing Limited, 2020)
Advances in Group Processes publishes theoretical analyses, reviews, and theory based empirical chapters on group phenomena. The series adopts a broad conception of 'group processes.' This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, trust, justice, social influence, identity, decision-making, intergroup relations and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, economics, business, philosophy, computer science, mathematics and organizational behavior. Volume 37 brings together papers related to a variety of topics in small groups and organizational research. The volume includes papers that address theoretical and empirical issues related to consumer social privilege, group processes and disrupted environments, the use of time as a construct and the affective bases of self. Other contributions examine solving problems of cooperation, the effects of identity non-verification, and a series of papers addressing Stryker's identity theory. Overall, the volume includes papers that reflect a wide range of theoretical approaches from leading scholars who work in the general area of group processes.
Chapter 1: Hypocognition and the invisibility of social privilege; Kaidi Wu and David Dunning -- Chapter 2: Group dynamics in disrupted environments; Lisa Troyer and Arwen H. DeCostanza -- Chapter 3.Where did the time go?: Insights on the meanings and uses of time in sociological social psychology; Reef Youngreen and Joseph Silcox -- Chapter 4.Grief, care, and play: theorizing the affective roots of the social self; Seth Abrutyn and Omar Lizardo -- Chapter 5: Reputation, forgiveness and solving problems of cooperation; Jane Sell, Katie Constantin and Chantrey J. Murphy -- Chapter 6: Negotiating a non-verified identity: emotional, cognitive, and behavioral responses; Brennan J. Miller and Will Kalkhoff -- Chapter 7: Identity theory: analysis and reconstruction; Barry Markovsky and Jake Frederick -- Chapter 8: Comment: getting identity theory (it) right; Jan E. Stets, Peter J. Burke, Richard T. Serpe and Robin Stryker -- Chapter 9: Reply: Where is it (identity theory)?; Barry Markovsky.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Social groups; Identity (Psychology); Social Science -- Sociology / Social Theory; Social groups